A Proposed Molecular Mechanism for Physical Analgesia in Chronic Pain - Norio Saito; Rei Shima; Yurika Yamada; Masaru Nagaoka; Etsuro Ito; Tohru Yoshioka (Neural Plasticity)
Although pain is indispensable for survival, chronic pain places a heavy burden on humans. As the efficacy of opioid treatment is limited, the development of alternative methods of pain relief without medication is desirable. Recently, we have developed a novel method of physical analgesia using an adhesive “pyramidal thorn patch.” When we apply about 3 trials of these patches on the skin of a pain region, the pain region moves toward the spinal cord like a “cutaneous rabbit,” and finally, the pain vanishes. In the present review, we propose a molecular mechanism for this analgesic method or pain relief following application of the pyramidal thorn patch where firstly the mechanoreceptors and their related nerves under the skin are activated in response to touch. Transient receptor potential (TRP) channels serve as mechanosensitive channels within these mechanoreceptors. We further propose that activation of the nerves connected with the mechanoreceptors releases oxytocin, which has an antinociceptive function and activates TRP channels to hyperpolarize the pain signal nerves. We believe that our system will pave the way for alternative pain treatment.